Pulmonary vasculopathy in explanted lungs from patients with interstitial lung disease undergoing lung transplantation. Issue 1 (12th July 2020) - Dotan, Yaniv; Stewart, Jeffrey; Gangemi, Andrew; Wang, He; Aneja, Amandeep; Chakraborty, Bhaidharbi; Dass, Chandra; Zhao, Huaqing; Marchetti, Nathaniel; D'Alonzo, Gilbert; Cordova, Francis C; Criner, Gerard; et al.
Abstract : Background: Pulmonary hypertension (PH) causes increased morbidity and mortality in patients with interstitial lung diseases (ILD). Classification schemes, while well-characterised for the vasculopathy of idiopathic PH, have been applied, unchallenged, to ILD-related PH. We evaluated pulmonary arterial histopathology in explanted human lung tissue from patients who were transplanted for advanced fibrotic ILD. Methods: Lung explants from 38 adult patients who underwent lung transplantation were included. Patients were divided into three groups: none, mild/moderate and severe PH by mean pulmonary artery pressure (mPAP) measured at pre lung transplantation right heart catheterisation (RHC). Grading of pulmonary vasculopathy according to Heath and Edwards scheme, and prelung transplantation evaluation data were compared between the groups. Results: 38 patients with fibrotic ILDs were included, the majority (21) with idiopathic pulmonary fibrosis. Of the 38 patients, 18 had severe PH, 13 had mild/moderate PH and 7 had no PH by RHC. 16 of 38 patients had severe pulmonary arterial vasculopathy including vascular occlusion with intimal fibrosis and/or plexiform lesions. There were no correlations between mPAP and lung diffusion with the severity of pulmonary arterial pathological grade (Spearman's rho=0.14, p=0.34, rho=0.11, p=0.49, respectively). Conclusions: Patients with end stage ILD had severe pulmonary arterial vasculopathy in their explanted lungs irrespective of the presence and/or severity of PH as measured by RHC. These findings suggest that advanced pulmonary arterial vasculopathy is common in patients with advanced fibrotic ILD and may develop prior to the clinical detection of PH by RHC.